Sistema web de gestión de mantenimiento vehicular al parque automotor del GAD municipal del cantón Bolívar - Mendoza Murillo, Karen Geovanna (2018)
The main objective of this degree work was to develop a web system for vehicle maintenance management at the municipal GAD Municipal Park of Bolívar canton for the permanent control of its units; to achieve this objective, the SCRUM methodology was selected, this methodology consists of different phases that helped to solve the established activities, and successfully concluded with the specific objectives set. The SCRUM methodology, as an important part for the development of this work, consists of three phases for its development such as: the planning of the iteration that consisted in conducting an interview with the personnel in charge of the machinery and fuel administration unit and the technology unit and public procurement; phase two, the execution of the iteration, which involves the development, it was structured and developed in SQL Management Studio 2012 and Visual Studio 2013 and phase three: Inspection and adaptation, in this phase the system was subjected to constant revisions by the SCRUM Master to make the respective changes. Once the vehicle maintenance management web system was tested and using the black box testing tool, it was concluded that the use of the vehicle management web system facilitated the management and access to the required information, in this way the degree work was completed in a satisfactory and punctualizing each and every one of the requirements established by the Municipal GAD of Bolívar canton.